Missionary Men in the Early Modern World: German Jesuits and Pacific Journeys - Strasser, Ulrike (Gendering the Late Medieval and Early Modern World, 2020)
Frontmatter --Table of Contents --List of Figures --Acknowledgements --Missionary Men on the Move --1 Manly Missions --2 Braving the Waves with Francis Xavier --3 Of Missionaries, Martyrs, and Makahnas --4 Martyrdom, Matrilineality, and the Virgin Mary --5 Writing Women's Lives and Mapping Indigenous Spaces --Conclusion and Epilogue --Bibliography --About the Author --Index